2016
DOI: 10.1111/jicd.12231
|View full text |Cite
|
Sign up to set email alerts
|

Treatment of periodontal intrabony defects using autologous platelet‐rich fibrin and titanium platelet‐rich fibrin: a randomized, clinical, comparative study

Abstract: The present study demonstrated that marked improvements in the clinical parameters and radiographic outcomes were noted with both autologous PRF and TPRF in the treatment of IBD.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

12
39
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 42 publications
(52 citation statements)
references
References 12 publications
12
39
1
Order By: Relevance
“…In the present study, the intra-group comparison revealed a significant original defect fill in both the T-PRF and L-PRF groups. In contrast, inter-group comparisons significantly favored the T-PRF group, which is quite different from the results reported by Chatterjee et al, 19 who found a higher percentage of defect fill for T-PRF with no significant difference. Moreover, the results of inter-group comparisons concerning original defect fill are different from the results reported by Mitra et al, 29 who showed no significant difference between the T-PRF and L-PRF groups.…”
Section: Discussioncontrasting
confidence: 98%
See 4 more Smart Citations
“…In the present study, the intra-group comparison revealed a significant original defect fill in both the T-PRF and L-PRF groups. In contrast, inter-group comparisons significantly favored the T-PRF group, which is quite different from the results reported by Chatterjee et al, 19 who found a higher percentage of defect fill for T-PRF with no significant difference. Moreover, the results of inter-group comparisons concerning original defect fill are different from the results reported by Mitra et al, 29 who showed no significant difference between the T-PRF and L-PRF groups.…”
Section: Discussioncontrasting
confidence: 98%
“…30 In the present study, intra-group comparisons showed a significant decrease in PPD from baseline to 9 months in both the T-PRF and L-PRF groups, whereas inter-group comparisons revealed nonsignificant differences. This was consistent with Chatterjee et al, 19 Sharma and Pradeep 8 , and Patel et al 31 However, the mean reduction in PPD values of the L-PRF group in the present study was higher than that in a study by Patel et al, 31 where the followup period was one year. Thus, PRF (both T-PRF and L-PRF) serves as a reservoir for growth factors and cytokines, which decrease the levels of matrix metalloproteinase-8 and interleukin-1β and increase tissue inhibitors of matrix metalloproteinase-1 levels, resulting in periodontal soft tissue healing.…”
Section: Discussionsupporting
confidence: 92%
See 3 more Smart Citations